Hydrodynamic of two immiscilible liquid flow system : biodiesel synthesis - Kau Mun Kit, Joshua (2015)
The hydrodynamic study of two immiscible liquids-liquid flow system is essential, especially in the liquid-liquid extraction process during biodiesel synthesis. This work aims to determine variable hydrodynamic parameter such as the liquid holdup fraction and dispersibility factor in two immiscible liquid-liquid flow system (namely palm oil and ethanol employed during biodiesel synthesis). A hindrance, which is the mass transfer limitation coexisted within the liquid-liquid flow system. The formation of emulsion layer which occurred when the organic phase expanded and the polar phase inversion occurs under vigorous stirring, resisted the upwards flow of ethanol to the decanter top and subsequently, inhibits the formation of FAEE. An agitated column with 6-bladed impellers was employed under a counter-current flow condition where the heavier palm oil phase was filled in the bottom decanter whereas the lighter ethanol was filled from the top decanter. Different feed flow rate and stirring speed were tested to identify the hydrodynamic variables. The ratio of feed flow (ethanol to palm oil) includes 1:1, 1:3, 3:1, 1:5 and also 5:1 whereas the stirring speed experimented were 300 and 500 RPM. It was observed that the lighter phase liquid holdup decreased along the number of stages for palm oil-to-ethanol flow ratio of 1:1, 1:3, 3:1, 1:5 and 5:1 with stirring speed 300 RPM. Similar trend can be observed with stirring speed 500 RPM. The distribution of these two phases were identified by determining the dispersibility value, wherein it was found that the dispersibility decreased along the stages together with increasing stirring speed. Noted also that the dispersibility decreased as the palm oil-to-ethanol flow ratio increased.